A Clinical Report of Two Cases of Cryptogenic Brain Abscess and a Relevant Literature Review - Zhou, Wei; Shao, Xuefei; Jiang, Xiaochun (Frontiers in Neuroscience, 2019)
Brain abscess, a severe intracranial infectious disease, refers to the parenchyma abscess caused by local infection or remote spread. Recently, advancements in modern medicine, especially the wide application of antimicrobial drugs, have contributed to the gradual decrease in the prevalence of this disease. However, cases of cryptogenic brain abscess that feature an unknown origin and atypical symptoms are rising. In this retrospective study, we report and analyze two cases of cryptogenic brain abscess. The first patient was a 30-year-old healthy man who was admitted to our hospital due to 1 week of headache and 3 days of headache aggravation, accompanied by nausea and vomiting. Head MRI shows a circular space-occupying as well as apparently enhanced DWI signals were observed in the right parietal lobe, and the ring wall manifested an apparent increase in signal intensity after enhancement. The patient was diagnosed as a brain abscess before operation and given craniotomy. The postoperative pathology confirmed brain abscess and recovered well after surgery. The second patient was a 45-year-old healthy woman who was hospitalized in a local hospital due to symptoms of headache and right limb weakness for 1 week. Head MRI shows a circular space-occupying lesion in the left basal ganglia, and the ring wall manifested an apparent increase in signal intensity after enhancement. The patient was suspected of glioma at the local hospital and was transferred to our hospital. Twelve hours after hospitalization, the patient was suspected of developing cerebral palsy and thus underwent emergency surgery including lesion resection in the left basal ganglia, resection of the polus temporalis, and a decompressive craniotomy. Postoperative pathology confirmed brain abscess. The patient was eventually conscious, but left the right limb hemiplegia. Hence, when a patient develops the classical triad of fever, headache, and focal neurologic deficits, the possibility of brain abscess should be investigated. Early diagnosis and treatment are crucial to minimize various complications and the number of deaths.